2021
DOI: 10.1007/s10499-021-00677-7
|View full text |Cite
|
Sign up to set email alerts
|

A review article on nanotechnology in aquaculture sustainability as a novel tool in fish disease control

Abstract: In recent decades, aquaculture has played a significant role in fulfilling the vast demand for animal protein requirements and consequently in food security. However, environmental contamination and disease prevalence are considered essential challenges for the sector. In this regard, new approaches have been paved in technology to deal effectively with such challenges. Among these, nanotechnology-as a novel and innovative tool-has a broad spectrum of uses and a tremendous potential in aquaculture and seafood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 102 publications
0
30
0
Order By: Relevance
“…They showed that oral nanovaccines can be used in fish aquaculture (Angulo et al 2020 ). Another recent study reported that selenium nanoparticles have proven to be a novel tool for controlling various bacterial as well as viral fish diseases (Nasr-Eldahan et al 2021 ).…”
Section: Types Of Vaccines For Fish Pathogens In Aquaculture and Thei...mentioning
confidence: 99%
“…They showed that oral nanovaccines can be used in fish aquaculture (Angulo et al 2020 ). Another recent study reported that selenium nanoparticles have proven to be a novel tool for controlling various bacterial as well as viral fish diseases (Nasr-Eldahan et al 2021 ).…”
Section: Types Of Vaccines For Fish Pathogens In Aquaculture and Thei...mentioning
confidence: 99%
“…In this study, chitosan was remarkably noticed as a proper biomolecule for derivatizing nanotubes. The biological function of chitosan and its derivatives (such as glycated chitosan, sulfated chitosan and trimethyl chitosan) have contributed to the immunostimulatory effect, and thus, it has been applied as a vaccine adjuvant and biologics delivery system [ 62 , 63 , 64 , 65 ]. However, even though HACF also contains chitosan, its immunostimulation and protection were not as similar as HCF.…”
Section: Discussionmentioning
confidence: 99%
“…Nanotechnology, as a novel and revolutionary technique, offers a wide range of applications and enormous potential in aquaculture and seafood preservation. It has the potential to develop new technologies for drug management and vaccine development, ensuring the protection of fisheries resources against disease-causing microorganisms (Nasr-Eldahan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%